Rethinking Adaptive Governance in Living Cultural Heritage Tourism: Insights from Majapahit Tourist Village, East Java - Evio Tanti Nanita; Ansh Sharma (Indonesian Tourism Journal, 2025)
In Indonesia, the safeguarding of living cultural heritage has been predominantly shaped by state-driven initiatives; however, the effectiveness of these top-down programs often falls short due to institutional fragmentation and limited grassroots participation. Majapahit Tourist Village in Mojokerto, East Java, established through the Majapahit Cultural House program which illustrates these persistent challenges, as numerous heritage houses have either deteriorated or been repurposed, exposing a disconnection between policy formulation and local implementation. This study investigates how adaptive governance can enhance the management of community-based cultural heritage tourism by analyzing the socio-political dynamics, local responses, and adaptive mechanisms at play within Majapahit Village. Utilizing a qualitative case study methodology, the research draws on in-depth interviews, direct observations, and policy document analysis. Through thematic analysis, the study identifies varying forms of community adaptation, spanning compliance, negotiation, and innovation that demonstrate local resilience in preserving cultural identity under socio-economic constraints. Results show that adaptive governance materializes through informal leadership, cultural entrepreneurship, and hybrid collaborations between community actors and external agencies. Nonetheless, the absence of coherent legal frameworks and insufficient financial support remain key obstacles to long-term sustainability. The study concludes that fostering adaptive governance necessitates co-management arrangements, participatory policy design, and the integration of cultural, economic, and legal considerations.